Knowledge, Attitude, And Practice in Diabetic Kidney Disease Prevention and Its Associated Factor Among Type 2 Diabetes Mellitus Patients in Northeast Peninsular Malaysia - Bin Rosedi, Anas; Mohd Yusoff, Siti Suhaila; Hairon, Suhaily Mohd; Mohammad Basir, Mohammad Fazrul (National Journal of Community Medicine, 2025)
Introduction: Diabetic kidney disease (DKD) is a major complication among Type 2 Diabetes Mellitus (T2DM) patients. Understanding their knowledge, attitude, and practice (KAP) of DKD prevention is crucial for guiding effective interventions. This study aimed to assess the level of KAP in DKD prevention and identify the factors associated with poor KAP among T2DM patients in Northeast Peninsular Malaysia. Methods: A cross-sectional study was conducted among 600 T2DM patients from government health clinics in Kelantan, Malaysia. Data were collected using a validated questionnaire, and logistic regression analyses identified factors associated with poor KAP, considering socio-demographic and clinical characteristics. Results: Findings showed 77.0% had poor knowledge, 58.2% poor attitude, and 37.7% poor practice. Poor knowledge was associated with single/divorced marital status, lower education, and diabetic complications, while unemployed participants had lower odds of poor knowledge. Poor attitude was linked to poor knowledge, lower education, and unemployment, while poor practice was associated with non-Malay ethnicity, lower education, and poor attitude. Conclusion: Targeted educational interventions are needed, focusing on vulnerable groups with lower education and specific socio-demographic factors to enhance DKD prevention and improve T2DM patient outcomes.